Observation of bosonic condensation in a hybrid monolayer MoSe2-GaAs microcavity - Max Waldherr (Nature Portfolio, 2018)
Atomically thin transition metal dichalcogenides are an ideal platform to investigate the underlying physics of strongly bound excitons in low dimensions. Here, the authors demonstrate the formation of a bosonic condensate driven by excitons in two-dimensional MoSe2 strongly coupled to light in a solid-state resonator.